The Effect of Knowledge Sharing Partners, Leadership Support on the Success of Knowledge Management and Organizational Innovation Performance - Rodhiah Rodhiah; Nur Hidayah (Britain International for Academic Research (BIAR-Publisher), 2022)
This study aims to determine the effect of peer/peer knowledge sharing on the success of knowledge management. The influence of leadership support on the success of knowledge management Researched 100 SMEs domiciled in the city of Tangerang as research samples, which were selected using purposive sampling technique. Data collection techniques by distributing questionnaires via google form. The analysis technique uses SEM with the Smart PLS program. The results showed: Sharing knowledge of colleagues on the success of SME knowledge management did not have a significant effect; Leadership support on the success of knowledge management has a significant influence; Leadership support for peer knowledge sharing has a significant effect; The success of knowledge management has a significant influence on innovation performance.